Long-term seropositivity, safety, and impact of inactivated and live, attenuated hepatitis a vaccines in China – A cross-sectional study. Issue 52 (14th December 2020) - Xiaojin, Sun; Rodewald, Lance E.; Guomin, Zhang; Hui, Zheng; Ning, Miao; Fuzhen, Wang; Zundong, Yin
Highlights: Live, attenuated and inactivated hepatitis A vaccines are both immunogenic and show long-term duration of protection. Live, attenuated and inactivated hepatitis A vaccines have similar per-dose safety profiles. Use of either vaccine results in similar population immunity and low incidence of hepatitis A. Abstract: Background: In 2008, China introduced live, attenuated hepatitis A vaccine (L-HepA, licensed in 1992) and inactivated hepatitis A vaccine (I-HepA, licensed in 2002) nationwide, and is currently the only country using L-HepA in routine immunization. We assessed seropositivity and its duration following vaccination, safety, and association with hepatitis A incidence and population seroprevalence for I-HepA and L-HepA. Methods: We obtained seroprevalence data from two nationwide serosurveys (in 1992 and 2014), vaccination status from the 2014 serosurvey, and vaccine safety and disease incidence data from the national surveillance system. We compared long-term HAV seropositivity among vaccine recipients and described safety profiles of both vaccines. We categorized the 31 provinces into those predominately using I-HepA and achieving high coverage (n = 4), those predominately using L-HepA achieving high coverage (n = 4), and those predominately using L-HepA achieving lower coverage (n = 23). We compared population HAV seropositivity, coverage, and disease incidence among the three groups. Results: One year after vaccination, seropositivity from I-HepA was significantly higher than from L-HepA (97.8% vs 90.7%), and seropositivity declined to 73.5% for L-HepA and 75.4% for I-HepA after 10 years – not significantly different by vaccine. The annual incidence of serious AEFI was <0.5/100 000 for both vaccines. Prior to licensure of either HepA vaccine, provinces that would go on to predominantly use I-HepA had lower incidences of hepatitis A and lower seropositivity levels to HAV than provinces that would go on to use L-HepA. By 2014, these differences were significantly diminished. Regardless of vaccine selection, all three province groups had lower immunity to HAV among individuals born during the 10 years prior to nationwide vaccine introduction – individuals who were 10 to 24 years old in 2014. Conclusion: Evidence of good immunogenicity, safety, and impact on incidence supports continued use of both I-HepA and L-HepA in the EPI system. These results may be useful for countries considering integrating HepA vaccines into their routine programs.